2014
DOI: 10.1007/s10895-014-1475-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Titration Assay of Affinity of Tight-Binding Nonfluorescent Inhibitor of Glutathione S-transferase

Abstract: To determine inhibition constant (K(i)) of tight-binding inhibitor, the putative method estimated an apparent K(i) from the response of initial rates to total concentrations of the inhibitor considering its depletion during binding for conversion into the true K(i), but was impractical with glutathione S-transferase of sophisticated kinetics. A fluorometric titration assay of dissociation constant (K(d)) was thus proposed. Schistosoma japonicum glutathione S-transferase (SjGST) action on a nonfluorescent dival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…GST was effectively inhibited by CAPE, with a K i value of 0.453 nM (Table 1). It was reported that the inhibitor of GST-bearing suitable linkers could concomitantly bind to two active sites of GST and usually possess K i values at nanomolar levels and excellent enzyme-selectivity 138 .…”
mentioning
confidence: 99%
“…GST was effectively inhibited by CAPE, with a K i value of 0.453 nM (Table 1). It was reported that the inhibitor of GST-bearing suitable linkers could concomitantly bind to two active sites of GST and usually possess K i values at nanomolar levels and excellent enzyme-selectivity 138 .…”
mentioning
confidence: 99%
“…On the other hand, eqn (11) always applies for the same C PF under competitive binding in the same interaction system; thus, eqn (12) applies when C XF /C XT < 10% is validated. With C PF negligible to C XT for the desired LOQ, the difference between C PT and C RBU is an approximate of C XBU ; therefore, eqn (13) applies.…”
Section: Resultsmentioning
confidence: 92%
“…The fluorescence of the tryptophan residues in GST at 340 nm under excitation at 280 nm was susceptible to the binding of ligands. Binding ratios of the divalent conjugate from BDEA plus excess GSH to GSTM and GSTA were thus estimated via fluorometric titration 36 . GSH, BDEA and their conjugate had negligible fluorescence signals at 340 nm under excitation at 280 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition constant ( K i ) of the divalent conjugate of BDEA to GSTM was estimated. After pre-incubation of the purified divalent conjugate with GSTM alone for 10–30 min to achieve divalent binding, the analysis of the responses of residual activities of GSTM to the total concentrations of the divalent conjugate, according to a model for a slow tight-binding inhibitor (Methods Equation (1)) 27 , 36 , gave an apparent K i of (0.48 ± 0.04) nM ( n = 3). The divalent conjugate of BDEA and GSH was thus a slow tight-binding inhibitor to GSTM with the highest affinity in searchable data 8 , 10 , 17 , 22 , 24–27 , 29 , 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation